Comparative Study of the Cultural Construction of Vocational Education and Training in Norway and Nigeria - Opara, Jacinta A (Mediterranean Journal of Social Sciences, 2012)
Despite the emergence of a common agenda for vocational education and training across many countries, it isincreasingly recognized that policy in practice varies significantly according to national context. Of course, it is one thing todevelop grand visions of the vocation education and training society within official policy documents, translating such visions intoreality usually turns out to be rather more problematic. This paper evaluated the pedagogical legacy of vocation education andtraining in these countries by analyzing the contribution of teachers and students to the development of VET based on theenrichment of historical and cultural environment. Norway had encountered difficulties in attempting to further progress thecause of vocational education and training. Nigeria to reach â€œthe positionâ€ might be a very strong statement because of differentsituations, cultures, etc. Nigeria to work toward a goal to which Norway offers a good model could be more realistic.